Gamicards - An alternative method for paper-prototyping the design of gamified systems - Ferro, L.; Walz, Steffen; Greuter, S. (2014)
This paper introduces an early prototype concept known as Gamicards, for use in the design of gamified systems. With the popularity of gamified approaches and the varying knowledge of designers of these systems, not enough resources exist that can assist to guide designers through the process, ensuring important elements (such as motivation) are considered. Gamicards are an early prototype deck of cards that are designed to provide a resource for designers from a range of different backgrounds and knowledge of gamified design, with the intention to develop more meaningful gamified approaches.